Humic substances and urea use in agriculture - Ahmad, Osumanu Haruna (Universiti Putra Malaysia Press, 2014)
This book serves as a quick reference text for agriculturists, environmentalists, students and early career researchers. Chapter 1 gives an overview of nutrient use efficiency while Chapter 2 details what humic substances are. Some of the major sources of humic substances are discussed in Chapter 3. The isolation and characterization of humic substances are covered in Chapter 4. Aspects such as extraction, fractionation, purification, and characterization of humic substances from different sources are discussed in Chapter 5. Chapter 6 focuses on control of ammonia volatilization using humic substances isolated from different sources while the effects of the humic substances on nutrient use efficiency, crop growth and development as well as their effects on soil chemical properties are dealt with in Chapter 7.